Microwave-Assisted Synthesis of CuZnS Nanocrystals for Spectrally Flat Visible Light Photodetector Application Using a ZnO/CuZnS Heterojunction - Dahiya S.; Singh S.V.; Pandey U.; Hazra S.; Pal B.N. (My University, 2025)
A microwave-assisted technique has been opted for scalable synthesis of ternary copper zinc sulfide nanocrystals (CZS NCs) and utilized for visible light photoconductor fabrication. These CZS NCs comprise 2D hexagonal sheets of ∼60 nm in approximate edge with a thickness of ∼9 nm, in combination with smaller size nanoparticles with an average size of ∼13 nm. The absorption spectra of CZS NCs demonstrated broad absorbance ranging from 300 to 750 nm, and the calculated bandgap of CZS NCs was found to be 1.65 eV. To realize their applicability in electronic devices, a lateral heterostructure photoconductor has been fabricated in a photoconductor geometry by using a sol-gel-derived ZnO thin film as a charge transport layer. The external quantum efficiency (EQE) at a 10 V external bias was approximately 10% within the range of 350 to 750 nm, whereas the device has a responsivity and detectivity of 4 A/W and 1 × 1012 Jones within that range, respectively. The device has a higher EQE (25%) with detectivity (1.6 × 1012 Jones) within the 300-350 nm range due to the photocurrent generation from ZnO. © 2024 American Chemical Society